Pemodelan Spasial Deforestasi Di Kesatuan Pengelolaan Hutan Lindung (KPHL) Unit VI Dolago Tanggunung Provinsi Sulawesi Tengah - Rhamdhani Rhamdhani; Akhbar Akhbar; Hasriani Hasriani (Universitas Tadulako, 2020)
This research intend to analyzing the process of deforestation, constraction of deforestation model and analyzing the factors of deforestation in protection forest management unit (PFMU) Unit VI Dolago Tanggunung Central Sulawesi. This research was carried out with analyzing change to cover the land by using landsat imagery. Deforestation analysis was carried out by making a spatial model using six factors namely distance from road, distance from river, slop, elevation, settlement, and population density using the Binary Logistic Regression method from January to April 2019. Results of land cover classification period of 2007 had a class namely primary dryland forest, secondary dryland forest, dryland agriculture, mixed dryland agriculture, rice fields, and shrubs. While the period of 2017 primary dryland forest, secondary dryland forest, dryland agriculture, mixed dryland agriculture, settlements and shrubs. The choosen model had the greatest score of goodness of fit and chi square. The results of binary logistic regression showed the score of goodness of fit was 27425017.29 the chi square score was 34341,2655 and pseudo r2 was 0.2091 greater than 0.2 which shown the model was feasible to use. The establishment of a spatial model of deforestation in the Protection Forest Management Unit (PFMU) Unit VI Dolago Tanggunung produce 5 variable factors consisting of accessibility aspects namely elevation, population density, river, slope, road. Logit (p) = -3.99930582 + 0.00000894 (x1) - 0,00022225 (x2) + 0,000000 (x3) + 0,00049952 (x4) + 0,000000 (x5)